Corticobasal and ataxia syndromes widen the spectrum of C9ORF72 hexanucleotide expansion disease. (4th July 2012) - Lindquist, SG; Duno, M; Batbayli, M; Puschmann, A; Braendgaard, H; Mardosiene, S; Svenstrup, K; Pinborg, LH; Vestergaard, K; Hjermind, LE; Stokholm, J; Andersen, BB; et al.
<x xml:space="preserve">Abstract</x> Recently, a hexanucleotide (GGGGCC) repeat expansion in the first intron of C9ORF72 was reported as the cause of chromosome 9p21‐linked frontotemporal dementia‐amyotrophic lateral sclerosis (FTD‐ALS). We here report the prevalence of the expansion in a hospital‐based cohort and associated clinical features indicating a wider clinical spectrum of C9ORF72 disease than previously described. We studied 280 patients previously screened for mutations in genes involved in early onset autosomal dominant inherited dementia disorders. A repeat‐primed polymerase chain reaction amplification assay was used to identify pathogenic GGGGCC expansions. As a potential modifier, confirmed cases were further investigated for abnormal CAG expansions in ATXN2. A pathogenic GGGGCC expansion was identified in a total of 14 probands. Three of these presented with atypical clinical features and were previously diagnosed with clinical olivopontocerebellar degeneration (OPCD), atypical Parkinsonian syndrome (APS) and a corticobasal syndrome (CBS). Further, the pathogenic expansion was identified in six FTD patients, four patients with FTD‐ALS and one ALS patient. All confirmed cases had normal ATXN2 repeat sizes. Our study widens the clinical spectrum of C9ORF72related disease and confirms the hexanucleotide expansion as a prevalent cause of FTD‐ALS disorders. There was no indication of a modifying effect of the ATXN2 gene.